ON THE EVOLUTION AND RECENT CHANGES IN THE STRATEGIC RELATIONS OF CENTRAL ASIAN COUNTRIES WITH THE EUROPEAN UNION (E Global Congress, 2025)
The growing environmental challenges of the 21st century have pushed businesses to rethink their operational strategies and adopt more sustainable practices. This thesis explores the concept of Green Management as an emerging managerial approach that integrates environmental responsibility into core business decision-making. It analyzes the principles of ecological sustainability, green leadership, and eco-innovation, offering a framework for organizations to align profitability with ecological consciousness. The study evaluates both the theoretical underpinnings and real-world practices of green management across different industries.